ANALISIS KOMPARATIF KINERJA KEUNGAN ANTARA PT SAMUDERA INDONESIA TBK DAN PT WINTERMAR OFFSHORE MARINE TBK YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015 - 2024 - Hendra, Hendra; Puji Muniarty (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to compare the financial performance of PT Samudera Indonesia Tbk and PT Wintermar Offshore Marine Tbk listed on the Indonesia Stock Exchange. Financial performance is measured using liquidity (Current Ratio), profitability (Return on Assets), and solvency (Debt to Equity Ratio). This research uses a descriptive comparative method with a quantitative approach. The data are obtained from the companies’ financial statements for the period 2015–2024. The results show differences in financial performance between the two companies, where PT Samudera Indonesia Tbk tends to have higher profitability, while PT Wintermar Offshore Marine Tbk shows improvement in liquidity and solvency.